Relationship between High Sensitivity-C Reactive Protein Level and Impaired Cognitive Function in HIV Patients - Kurniawati, Rachmi; Sugianto, Paulus (Folia Medica Indonesiana, 2021)
Human Immunodeficiency Virus (HIV) infection was one of the most serious health challenges in the world. The Ministry of Health of the Republic of Indonesia reports the number of HIV cases in Indonesia as of June 2019 as many as 349,882. At present, although antiretroviral combination therapy has been found, the prevalence of neurocognitive disorders in the form of HIV-associated neurocognitive disorders (HAND) reaches 50% of HIV patients. This study aimed to determine the relationship between high sensitivity-C Reactive Protein (hs-CRP) level and cognitive impairment assessed using MoCA-INA score in HIV patients at the UPIPI Dr. Soetomo Academic Hospital Surabaya. This cross-sectional study used consecutive sampling that fulfilled inclusion and exclusion criteria. The cognitive function of the subjects was examined by MoCA-INA score and blood samples were collected for measuring hs-CRP level. Of 100 subjects, 41 had abnormal MoCA-INA score and 59 had normal score. The number of subjects with high level of hs-CRP (>= 5) who had abnormal and normal MoCA-INA score were 22 (53,7%) and 6 (10,2%) respectively. This result was significantly difference with p = 0,0001, RO = 28,072 (95% CI, 5,470-144,052). Therefore, there was a significant relationship between hs-CRP level and cognitive function, where a subject with a high hs-CRP level was more likely to have impaired cognitive function.